Virgin Mary’s Importance in Islam and its Reflection on Classical Turkish Literature and Turkish Language - Koçin, Abdulhekim (Journal of History Culture and Art Research, 2017)
The language used by a poet or an author in a literary work in verse or prose, and the way he uses idioms, proverbs and literary arts in that language indicate the success of his art. The achievement of author in this matter makes him well known in the country where he lives. However, the topic choice is as important as an artist’s language skills. That’s why poets and authors prefer universal subjects such as love, death, religion, religious personalities (like prophets, saints, etc.) and humanity (man's way of living and right to live) in their works. If artists produce universal subjects with a clear language, a fluent wording and a strong story line, this achievement makes them famous both nationally and internationally. This fact can also be applied to the literature of any nation. Literary works containing local subjects cannot take their place in the world’s literary history. Classical Turkish literature (Ottoman Period Turkish Literature) is extremely rich in subject matter. The period in which Classical Turkish Literature continued its existence was the period when the Ottoman state dominated large geographical regions in Asia, Europe and Africa. Accordingly, the lifestyles, beliefs, traditions and customs of people from different religions, races and cultures living in these geographies; in other words, the issues that are important to these people were also reflected in the literature produced in this period. The subject of this article Virgin Mary is an important religious and a historical personality primarily for the Ottoman state’s Christians and Muslim subjects as well as those who weren’t the subjects of Ottoman Empire. In this article, first how Virgin Mary took part in the two most important sources of Classical Turkish literature, Koran and the hadiths will be summarized. Secondly, Virgin Mary’s place in Classical Turkish literature and the vocabulary and concepts that Turkish language gained through Virgin Mary will be tried to be detected by using the examples identified as related to Virgin Mary in collected poems of Classical Turkish literature’s main poets. In the end of the article, the results that are concluded to be related to the places of these two religious and historical personalities in Islam and their place in Classical Turkish literature under the influence of Islam will be presented point by point.